Response of a complex tropical pasture mixture to different grazing systems - E. Maraschin, Gerzy; O. Mott, Gerald (Pesquisa Agropecuaria Brasileira, 2014)
A pasture evaluation study was conducted at the University of Florida (USA) in 1974, to evaluate the effects of the management factors Grazing Days (GD). Rest Period (RP) and Grazing Pressure (GP), at five levels each, in a Central Composite experimental design. The complex tropical pasture mixture of siratro, greenleaf desmodium, lotononis and coastcross-1 bermudagrass, was established in 1973, and grazed by yearling Hereford x Zebu heifers. Dry matter yield and botanical composition were determined by double-sampling procedure, and the pasture responses were analized by a sacond degree polynomium. GD was the least significant factor. Longer RP favored the tropical legumes. The RP x GP encouraged the grasses, while high GP reduced the weed component. Maximum DM yields were determined by the RP x GP interaction as well as higher grazing capacity was attained at the higher GP level. By increasing GP levels increased IVOMD of the grasses and the siratro component, but the response for increasing RP was curvilinear. The N content of the grasses was reduced by increasing amounts af residue left after grazing, while that of the tropical legumes showed a quadratic response to increasing RP. These tropical legumes require long RP to be maintained on the pasture, while high GP works as a tool in the renewal of the pasture profile, increasing the opportunities for regrowth and better forage DM allowances.